PERANCANGAN INTERIOR RUANG PERPUSTAKAAN PERGURUAN TINGGI DI JAKARTA (STUDI KASUS PERPUSTAKAAN UNIVERSITAS MERCU BUANA) - Sahra, Sifa Aulia; Lelo, Lelo (Anggada : Jurnal Desain dan Seni, 2021)
Generally the library is a place to read books and add references about science and to add data to the task literature. Reading books or literature is a very important source of reference for students. But it is unfortunate that the interest in reading among students looks very minimal at this time. One of the low interest in reading is among students, it can be seen from the number of visitors in each college library. The library will look very crowded when just before the exam because many students are looking for books for reference sources of assignments, other than when not before the exam the library tends to be very quiet visitors, who visit the library are usually only a few final-year students who are working on thesis. the presence of a library with a comfortable room is very necessary to attract interest, especially students and the general public so they want to visit the library. The design method used is a qualitative analysis method whose data collection techniques are by means of observation, interviews, literature studies, comparative studies, documentation. The result of this design is the "Modern" style and the theme "Wonderful green and local culture of Betawi" in the interior of the College Library, by creating a functional atmosphere, ergonomic, and has a good aesthetic value, so that it can make the place become more convenient for visitors and also for employees on duty.